Modern sediment characteristics of Cua Dat Hydroelectric Reservoir based on high-resolution seismic data - Nguyen, Van Diep; Duong, Quoc Hung; Mai , Duc Dong; Bui, Viet Dung; Nguyen, Quang Dung (Vietnam Journal of Marine Science and Technology, 2024)
The Cua Dat Reservoir is located on the Chu river in Thuong Xuan district, Thanh Hoa Province, Vietnam. It was constructed to serve the Cua Dat hydroelectric power plant with a designed capacity of 97 MW. After ten years of operation (2010–2023), the water accumulation process has formed a modern sediment layer with its own characteristics. High-resolution seismic survey work was carried out using the EdgeTech 3400 Sub-bottom Profiler equipment within the reservoir area of the Cua Dat hydroelectric project, covering over 40 km of survey lines. The processed results and data analysis have revealed fundamental features of the terrain and modern sediment characteristics within the reservoir area. The study indicates that sediment upstream of the dam consist mainly of coarse materials (sand, gravel, etc.) deposited in a medium to weak hydraulic environment with short cycles and very low deposition rates, frequently re-settled due to hydraulic dynamics. The weak cohesion of the sediment materials often causes localized surface slumping phenomena with significant amplitudes, extending up to several meters, disrupting the equilibrium trend of sedimentation and leading to an accumulation of sediment towards the dam intake culvert. These observations provide insights into the dynamics of the reservoir surface sediment environment, while also demonstrating that current reservoir operation and exploitation conditions can ensure longevity and safety as per the design of the Cua Dat hydroelectric project.